Fanny Haussman (1818-1853) - biografija prve slovenske pesnice v luči njenega domnevno spornega avtorstva - Buttolo, Frančiška (Slavistična revija, 2010)
A biography of Fanny Hausmann (1818-1853), a poet of German origin, presents her youth in her birthplace to her move to Žalec (1835), her acculturation to the Slovene environment and language (up to 1842), and her encounter with Slovene and South Slavic literatures (1843-1847), her publications in the liberal Celjske slovenske novine (ed. V.Konšek) at the time of the revolution of 1848-1849, as well as the end of her publishig days, her illness and subsequent death (1850-1853). The alleged controversy surroundig her authoship (I. Orožen, F. Ilešič. I. Grdina) is examined together with a survey of her life and work.
Keywords: 1848; 19.st.; Hausmann, Fanny, 1818-1853; history of literature; ilirsko gibanje; literarna zgodovina; Romanticism; romantika; Slovene literature; slovenska književnost; slovenska poezija; slovenske pesnice